The People's Two Bodies: An Alternative Perspective on Populism and Elitism. (December 2018) - Fumurescu, Alin
Inspired by the late medieval doctrine of the King's Two Bodies, the idea of the People's Two Bodies has been so far used lightly by scholars, mostly to point out a supposed contradiction in our shared assumptions about "the people." The essay argues that the People's Two Bodies paradigm is more than a mere linguistic artifice, proving useful for dealing with the pitfalls of elitism and populism while taking advantage of both approaches. It shows that the dual understanding of "the people, " both as a multitude and as a corporate whole, enjoys actually a long pedigree in the history of political thought. As such, the paradigm of the People's Two Bodies helps address some of the major theoretical and practical challenges that liberal democracies are facing today.